2023
DOI: 10.1097/jcn.0000000000001023
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Cognitive Training and 24-Month Mortality in Heart Failure

Abstract: Background Cognitive dysfunction predicts mortality in heart failure (HF). Computerized cognitive training (CCT) has shown preliminary efficacy in improving cognitive function. However, the relationship between CCT and mortality is unclear. Aims were to evaluate (1) long-term efficacy of CCT in reducing 24-month mortality and (2) age, HF severity, global cognition, memory, working memory, depressive symptoms, and health-related quality of life as predictors of 24-month mortality among patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…A hallmark of JCN has been the outstanding research that advances heart failure nursing including landmark heart failure self-care theory, 6–8 innovative interventions, 9–11 and advances in heart failure symptom science 12–15 . These articles, along with a collection of heart failure caregiver research, can be found in the special collections section of the JCN website.…”
mentioning
confidence: 99%
“…A hallmark of JCN has been the outstanding research that advances heart failure nursing including landmark heart failure self-care theory, 6–8 innovative interventions, 9–11 and advances in heart failure symptom science 12–15 . These articles, along with a collection of heart failure caregiver research, can be found in the special collections section of the JCN website.…”
mentioning
confidence: 99%